The Effect Of Excessive Screen Time On Early Childhood Emotion Regulation At Paud Al-Irsyadah - Alfa Rohmatin; Raihan Ahlush Shuffah; Nazwa Nurul Fatma; Sri Zulfa Laeliyah Bilqis Tadzkir Putri (FKIP UNSULTRA, 2026)
Excessive gadget use in early childhood has become a growing concern because it may reduce direct social interaction and limit children’s opportunities to practice emotional control in daily situations. This study aimed to determine the effect of excessive screen time on the emotional regulation development of early childhood students at PAUD Al-Irsyadah. The novelty of this study lies in examining the predictive effect of excessive screen time on emotion regulation using a quantitative regression approach in an early childhood education setting. This research used a quantitative approach with an associative design. The population and sample consisted of 30 children selected through total sampling. Data were collected using closed questionnaires measuring excessive screen time and emotional regulation. The instruments were tested through validity and reliability analysis, while the data were analyzed using descriptive statistics, correlation tests, and simple linear regression. The results showed that excessive screen time had a significant negative effect on children’s emotional regulation, with a significance value of 0.004. The regression model showed that excessive screen time explained 25.5% of the variance in emotional regulation (R² = 0.255). These findings indicate that higher screen exposure tends to be followed by lower emotional regulation skills. The findings contribute to understanding the role of digital media exposure in early childhood socio-emotional development and provide practical implications for parents and teachers in managing children's screen use through supervision, time limits, and meaningful social interactions.